COMMUNITY EMPOWERMENT IN THE SADARI PROGRAM (BREAST SELF-EXAMINATION) - suryanti, Suryanti; Khadijah, Siti (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2024)
Background: Cancer is currently one of the leading causes of death worldwide. One of the most common cancers and with the highest incidence is breast cancer. There are still many PKK Mojosongo Jebres Surakarta mothers who are not aware of the importance of early breast examination. This Breast Self-Examination (BSE) has been proven to be culturally acceptable, religiously friendly, and inexpensive. BSE is one way of action to find early symptoms of breast cancer that can be detected by mothers themselves, does not require experts to find breast cancer early, and is part of prevention efforts. Objective: This community service is to improve BSE knowledge and skills through community empowerment which will have an impact on increasing awareness and efforts to prevent breast cancer in Mojosongo. Methods: This activity begins with a regional visit to find out the existing problems, and a meeting with the PKK Chairperson to coordinate the implementation, the sampling technique uses a total sampling of all PKK mothers totaling 50 people who are given education and practice on how to do self-examination at home. Results: Community service can improve the ability of PKK mothers to do BSE independently. Conclusion: SADARI Education and Training improves the ability of knowledge and skills independently and has a positive impact on maternal health. The Recommendations, need to encourage and follow up on education and training on SADARI examinations by adding periodic follow-up sessions, this is done so that knowledge and practice of SADARI continue to be implemented.